Marginalised millennials: Conversation or conversion towards a Christian lifestyle in South Africa? - Knoetze, Johannes J. (HTS teologiese studies, 2018)
The World Council of Churches’ statement prepared by the Commission on World Mission and Evangelism, Together Towards Life: Mission and Evangelism in Changing Landscapes, states that mission from the margins calls for an understanding of the complexities of power dynamics. These power dynamics include global systems and structures, as well as local and contextual realities. One of the local contextual realities of South Africa is ‘a culture of violence’ against the vulnerable. Many millennials in South Africa – which constitute the majority of the current South African population – form part of the marginalised, not only in the global systems and structures but also in the local context. TLL acknowledges that Christian mission, and by implication the Christian church, largely failed to challenge economic, cultural and political systems that have marginalised many in the South African context, including the millennials. However, this article wants to study the millennials in South Africa from a missional church perspective regarding their views on culture, gender and violence and will attend to the following two issues: firstly, the role of culture in marginalisation, and secondly, the question about a proper response by the church, namely conversation or conversion?